Current and developing therapies for the treatment of non-small cell lung cancer with ALK abnormalities: update and perspectives for clinical practice. (21st November 2016) - Caccese, M.; Ferrara, R.; Pilotto, S.; Carbognin, L.; Grizzi, G.; Caliò, A.; Brunelli, M.; Cuppone, F.; Petraglia, S.; Scarpa, A.; Tortora, G.; Bria, E.
ABSTRACT: Introduction: The treatment of patients with ALK-rearranged non-small-cell lung cancer was completely revolutionized by the introduction of Crizotinib, a small molecule inhibiting ALK, MET and ROS1. Given that resistance occurs within approximately 12 months, in order to develop more potent inhibitors and to increase drug penetration to CNS, innovative ALK-inhibitors were developed. Second-generation ALK inhibitors Ceritinib (LDK378), Alectinib (CH5424802/RO5424802) and Brigatinib (AP26113) have shown significant clinical activity, and were rapidly approved by regulatory agencies. In addition, early clinical data demonstrated that 3 rd generation ALK-inhibitors Lorlatinib (PF-06463922), Entrectinib (RxDx-101) and Ensartinib (X-398) provided promising advantages in terms of both clinical activity and safety. Areas covered: In this review, the efficacy and tolerability of Crizotinib for 1 st and 2 nd -line treatment, and the clinical and preclinical data that led to the development of innovative second and third generation ALK-inhibitors are described. Expert opinion: The better characterization of the mechanisms of resistance to Crizotinib led to the development of newest drugs, which are active both after Crizotinib failure and in patients naïve from ALK-inhibitors. Tumor characterization at disease progression will allow to further personalize the treatment by establishing optimal sequences, which represent tough challenges for the future research in this field of cancer treatment.